Family empowerment model in pregnant adolescents in a primary care unit - Morales Oramas, Candy Gabriela; Avalos-García, María Isabel; Garrido Pérez, Silvia María Guadalupe; Sánchez Rodríguez, Rosa Maria; Rodríguez-Burelo, María del Rosario; Martínez-Pérez, Jorge Iván (Horizonte Sanitario, 2024)
Objective: To evaluate the effect of family empowerment on pregnant adolescents to face the pregnancy and motherhood process and improve family function.Materials and methods: Mixed process research in the multi-level concurrent Nested Design modality, where data were collected at different times, but the analyzes varied in each of these. It was developed in three stages: diagnosis-intervention-evaluation from January 2022 to January 2023. In the first stage, 50 adolescents participated, Family Apgar and DES28 Empowerment Scale were applied, after informed consent. In the second, the empowerment model was applied in four dysfunctional families without empowerment, with an average of ten sessions for each family and family work tools were used. In the evaluation stage, a quasi-experimental design was used with pretest-posttest of the family APGAR and empowerment scale. Descriptive and analytical statistics were used to capture and analyze the information (Pearson's X2, RP, Student's T), with the SPSS V25 statistical software.Results: Age Ⱦ=17, 17-19 years 80%, high school 46%, common law union 41%. Without empowerment 34%, family dysfunction 64%. Families without empowerment were 30% dysfunctional. The risk factors observed were: inadequate communication in the marital subsystem, addictions, chronic illness. Protective factors: attendance at a religious group, good personal and dietary hygiene, and choice of subdermal implant as a contraceptive method.Conclusions: The effect of the executed Model allowed empowering pregnant adolescents and improving family dynamics and function.Key words: Adolescent, Family dynamics, Empowerment.